Using wave runup modeling to inform coastal species management: An example application for sea turtle nest relocation. (1st May 2019) - Ware, Matthew; Long, Joseph W.; Fuentes, Mariana M.P.B.
Abstract: The inundation of foreshore and backshore coastal environments caused by wave runup or groundwater intrusion can be extremely detrimental for beach-dwelling organisms. For beach-nesting species, whose eggs require sufficient gas exchange with the surrounding environment for proper embryonic development, inundation for prolonged periods can result in embryonic mortality. Management strategies such as the relocation of nests high on the beach to avoid wave action have been applied for some species, though this strategy may result in unnecessary nest manipulation. To improve the identification of beach locations potentially exposed to inundation caused by wave wash-over which may require management action, wave runup models were tested in Fort Morgan, Alabama, USA for the 2016 sea turtle nesting season. The potential exposure of sea turtle nesting sites to wave wash-over was determined by comparing observed nest elevations to the predicted combined elevation of wave runup, tide, and surge (i.e., total water level). Total water level was calculated using three different definitions of beach slope: foreshore, nest, and dune-to-water (DTW), and two LiDAR-derived elevation estimates: the most recent survey from 2016 and a time-averaged digital elevation model (DEM). Models using the time-averaged DEM performed as well as, or better than, those using the 2016 LiDAR survey in the majority of comparisons. Wash-over state was correctly identified for up to 83.3% of sites when using nest slope in the wave runup calculation. However, DTW slope performed the best when predicting the wash-over frequency of a site. Mapping of the predicted 98th percentile of wave runup indicated that only 11.2% of nesting sites were exposed to wave wash-over, in contrast to the 21.3% of nests which were relocated. Wave runup models have not previously been used to inform sea turtle conservation actions; however, it holds promise for improved targeted management interventions and can assist other species (e.g., shorebirds, beach mice), which rely on dry beach habitat for nesting, feeding, and migratory rest stops. Wave runup models can also be used to investigate past storm events, forecast approaching storm impacts, and supplement sea level rise scenarios for coastal species management at multiple spatial scales. Highlights: Modeling wave runup has the potential to improve coastal species management. Models correctly identified up to 83.3% of washed-over sea turtle nesting sites. Time-averaged DEMs inform exposure risk even without up-to-date beach surveys. Optimal choice of beach slope varies with desired type of output specificity.